The topological proof of Abel-Ruffini theorem - Żołądek, Henryk (Topological Methods in Nonlinear Analysis, 2000)
We present a proof of the non-solvability in radicals of a general algebraic equation of degree greater than four. This proof relies on the non-solvability of the monodromy group of a general algebraic function.